Neonatal seizures and epilepsies - Vinayan, Kollencheri Puthenveettil; Moshé, Solomon L. (International Journal of Epilepsy, 2014)
Neonatal seizure is the most frequent clinical manifestation of central nervous system dysfunction in the newborn. It is defined as a paroxysmal alteration in neurologic function that include motor, behavior and/or autonomic functions occurring in the first 28 days after birth of a term neonate or before 44 weeks of gestational age in a preterm infant. Seizures in the presence of encephalopathy are the most important clinical pattern of an acute cerebral insult in the immature brain. Chronic epileptic disorders very rarely may have their onset in the neonatal period and may persist well into infancy and later childhood. Structural brain defects and metabolic disorders constitute a substantial proportion of this group. Ictal EEG recordings remain the gold standard for the accurate identification of neonatal seizures of cortical origin and for the distinction from non-epileptic paroxysmal events. This review focuses on the electroclinical patterns of neonatal seizures and epilepsies with an emphasis on the classification and terminologies. The current therapeutic options are also highlighted briefly.
Keywords: Newborn; Seizures; Epilepsies